A novel frameshift mutation in the PITX2 gene in a family with Axenfeld-Rieger syndrome using targeted exome sequencing - Lusi Zhang; Yingqian Peng; Pingbo Ouyang; Youling Liang; Huilan Zeng; Nuo Wang; Xuanchu Duan; Jingming Shi (BMC, 2019)
Abstract Background Axenfeld-Rieger syndrome (ARS) is an autosomal dominant genetic disorder that is characterized by specific abnormalities of the anterior segment of the eye. Heterozygous mutations in two developmental transcription factor genes PITX2 and FOXC1 have been identified within ARS patients, accounting for 40 to 70% of cases. Our purpose is to describe clinical and genetic findings in a Chinese family with ARS. Methods An ARS family with three affected members was recruited. The patients underwent a series of complete ophthalmologic examinations, general physical examination and dental radiography. DNA samples of proband II-1 were used for targeted exome sequencing of the FOXC1 and PITX2 genes. Sanger sequencing was used to validate the variation in PITX2. Quantitative real-time PCR was carried out to detect the expression of PITX2 in patients and normal controls. Results All affected members showed iris atrophy, corectopia, shallow anterior chamber, complete or partial angle closure, and advanced glaucoma. In addition, they revealed systemic anomalies, including microdontia, hypodontia, and redundant periumbilical skin. A novel heterozygous frameshift variation, c.515delA, in PITX2 was found in the proband, which might lead to a truncated PITX2 protein (p.Gln172ArgfsX36). Sanger sequencing validated that the variation completely cosegregated with the ARS phenotype among this family, but was absent in 100 unrelated controls. Quantitative real-time PCR analysis revealed that the mRNA expression of PITX2 was significantly decreased in patients compared with that in unrelated normal controls. Conclusions PITX2 c.515delA (p.Gln172ArgfsX36) was the genetic etiology of our pedigree. The mutation led to decreased PITX2 gene expression and a truncated mRNA transcript.